2005
DOI: 10.1097/00001504-200503000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for white matter abnormalities in schizophrenia

Abstract: Purpose of review-The purpose of this review is to highlight important recent imaging, histological, and genetic findings relevant to white matter abnormalities in schizophrenia. It is cast within the context of research findings conducted over the last 5 years, where we analyze their importance in understanding schizophrenia, as well as discuss future directions for research.Recent findings-White matter abnormalities have long been hypothesized in schizophrenia, although only recently has it become possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 72 publications
6
74
1
2
Order By: Relevance
“…Converging evidence suggests that myelin, and specifically oligodendrocytes, is in some way dysfunctional in schizophrenia [40,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence suggests that myelin, and specifically oligodendrocytes, is in some way dysfunctional in schizophrenia [40,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Since this original report, other studies have shown various signs of oligodendrocyte degeneration and myelin sheath abnormalities in prefrontal cortex in brains from patients with schizophrenia. 29,30 MRI studies using diffusion tensor imaging in vivo have indicated abnormalities in white matter in prefrontal cortex and other brain areas of patients with schizophrenia, indicating the possibility of disturbed maintenance of myelination through oligodendrocytes [31][32][33][34] although not all studies agree. 35,36 Recently, postmortem gene expression profiling has boosted the field by showing that many myelinrelated genes are downregulated in several brain regions of patients with schizophrenia compared with controls [37][38][39][40][41] Furthermore, it is interesting to note that while most of the myelination occurs shortly postnatally, 42 the peak of myelination in the cortical areas and especially in the prefrontal cortex occurs during the adolescence and early adulthood, 43,44 thus coinciding with a critical period for the onset of schizophrenia.…”
Section: Abnormalities In Myelination and Lipid Biosynthesis In Schizmentioning
confidence: 99%
“…Although there have been several reports of focal decreases in white matter density (Suzuki et al, 2002;Shapleske et al, 2002;Spaletta et al, 2003;Hulshoff Pol et al, 2004;Davatzikos et al, 2006), regional white matter volumes proper in patients with schizophrenia have not been frequently assessed (Shenton et al, 2001;Kubicki et al, 2005). This is primarily related to difficulties with its parcellation, given a lack of consensual anatomical landmarks or wholebrain partition schemes.…”
Section: Regional Morphometry In Patients With Schizophreniamentioning
confidence: 99%